LKPD Development Practicality on MEAs Based-Approach In Improving Mathematical Communication Ability Of Grade X Students - Putri Dewi Wardawati; Irwan Irwan; Jon Efendi (Universitas Negeri Padang, 2018)
The problems seen so far that at each level of tested questions requires different mathematical communication ability. Generally obtained the results of identification if the higher level of mathematics problems, the more the ability of mathematical communication explored student so that learning will become more meaningful. But Students work sheet used in the learning facilitate students’ to develop their mathematical communication ability. One alternative to overcome this is by designing LKPD based on the Model Eliciting Activities (MEAs) approach. This study porpuse to test LKPD practicability based on MEAs approach that has been validated by mathematicians, language and education technology. From the result of questionnaire respond learners and teachers obtained practical value 87.4% and 88.24% with very practical criteria. LKPD MEAs according to the students have very practical use because it can improve the mathematical communication ability, the material in LKPD can be understood for the achievement of learning objectives.